Immigration: The Potential Impact on EU Society - Gudrun Biffl (Austrian Institute of Economic Research (WIFO), 2005)
There is no simple answer to the question of the potential impact of migration on EU society. EU migration policy is expected to meet the requirements of economic and social policy, in particular of the Lisbon Agenda, as well as national cultural, political, strategic and security imperatives. The problem is complicated by different national traditions in social organisation, which are deeply rooted in history and which resulted in different migration models within the EU. As with employment, educational and social policy issues, the need to reach a common understanding about possible routes to eventual convergence, will call for coordination of the migration policies of the Member States (MS). Moreover, an issue in its own right is immigration as a tool to counter the negative impact of population ageing on economic growth and the pressure on public funds. While we know that immigration alone cannot solve the problem of population ageing, it can be an important policy instrument, complementary to other measures to raise the activity rate of older persons, and of prime age women. Its impact will depend on the level, composition and duration of inflows as well as the necessary measures which are to form an integral part of migration policy. Another aspect of migration concerns the internationalisation of production and its contribution to the diversification of the productive structure of the EU and its member states. Thus migrants impact on the supply side - the production potential of the economy - as well as on the demand side - the level and composition of consumption. Further, migration may also contribute to the growth of the informal economy, an aspect of concern in MS with high shares of the informal sector in GDP ...
Keywords: 330; Einwanderung; Migrationspolitik; EU-Mitgliedschaft; EU-Staaten